The consequences of American nuclear disarmament : strategy and nuclear weapons - Leah, Christine M. (Palgrave Macmillan, 2020)
Contents: Acknowledgments; Contents; Acronyms and Abbreviations ; List of Tables; Chapter 1: Nuclear Weapons: A Piece of the Peace; The Arguments for Abolition; On the Path to "Zero"; Notes; Chapter 2: Deterrence Without Nuclear Weapons?; Deterrence; General and Immediate Deterrence; Nuclear Deterrence; Political and Physical Challenges of Deterrence; Second-Strike Capability; Mutual Assured Destruction; Nuclear Superiority; Escalation, Escalation Control, Escalation Dominance; Damage Limitation; Countervalue Versus Counterforce Targeting; Extended Nuclear Deterrence; The Evolution of Precision Contents: The Limits of Deterrence; Conclusion; Notes; Chapter 3: Deterrence Without Nuclear Warheads?; Destruction and Delivery; The Controllability of War; The Nuclear-Missile Interaction: Implications for Deterrence; Missile Deterrence Without Nuclear Warheads?; The Importance of Missile Control; Conclusion; Notes; Chapter 4: Alliances Without Nuclear Weapons? (I); Alliance Theory; Level of Reliance; Vulnerability; The Consequences of "Conventionalizing" Nuclear Alliances; Conclusion; Notes; Chapter 5: Alliances Without Nuclear Weapons? (II): The Case of the Asia-Pacific Contents: A "Return" to Conventional Deterrence and Extended Deterrence?; The Asia-Pacific as a Test Case; Not Just Nuclear Weapons…; Geography and Extended Deterrence; Military Logistical Challenges; Fewer Nukes but More Conventional Forces?; Conclusion; Notes; Chapter 6: Arms Control Without Nuclear Weapons?; Concepts of Conventional Arms Control: Historical Examples; Current Regimes; The Absence of Arms Control in Asia; Conclusion; Notes; Chapter 7: Disarming the Peace?; Ceci N'est Pas "Zéro"…; Concepts of Nuclear Strategy and the Missile Revolution; Nuclear Weapons, Alliances, and Extended Deterrence Contents: "Friendly" Proliferation?; Japan; South Korea; Australia; The USA; Benefits and Disadvantages of Allied Proliferation; Expanded Nuclear Sharing?; The Challenges of Conventional Arms Control; Arms Control in Asia?; Modernization, Reductions, and Disarmament…; Nuclear Deterrence: Should the Mystery Be Kept Alive?; Deep Reductions: Could, and Should the USA Have a "Minimum Deterrence" Posture?; Conclusion; Notes; Bibliography; News Reports, Institutional Publications, National Archival Sources; Index